In-vivo Hepatoprotective Evaluation of Sicyos edulis on Wistar Albino Rats - Karisma Borah; Devid Chutia; Manodeep Chakraborty; Ananya Bhattacharjee; Nihar Ranjan Bhuyan (Krupanidhi College of Pharmacy, 2023)
The liver is known for synthesising enzymes, metabolism, and excretion of drugs and food. However, during biological processes, the abnormality occurs in the liver, which becomes a significant global health burden in humans, characterised by loss of synthetic function, breakdown of blood, irregular vitamin K, and localised, permanent changes to parenchymal cells. The study was designed to research the Phytochemical and biological screening of Sicyos edulis leaf for hepatoprotective activity on laboratory animals using paracetamol and methotrexate model for acute incidence. The study evaluated liver toxicity in healthy Wistar albino rats using two in vivo models. Each study group consists of six animals. In the first model, paracetamol p.o. for seven days. Similarly, in the second model, methotrexate was administered (single dose treatment) to animals with 20mg/kg, b.w., p.o. Both models were challenged with methanolic extract of Sicyos edulis leaf (MESEL) of doses 100mg/kg (low) and 200 mg/kg (high) p.o. for seven days, respectively. On day 8th, the blood samples were collected from the tail vein and analysed for various biochemical parameters. MESEL successfully restored the elevated serum biomarker levels in our study. The decrease in aspartate aminotransferase was observed by removing toxic metabolites, the reduction in alanine aminotransferase was due to an increase in ATP synthesis in mitochondria, thereby modulating the balance of liver energy metabolism, and the decrease in alkaline phosphates is due to tissue regeneration, an increase in total protein denotes the restoration of protein imbalance from acute liver injury. At different concentrations, all these effects strengthen the liver, regulate body metabolism, and ultimately inhibit further liver cell damage in favour of their regeneration. Our study also evidences the protective action of MESEL in rats against the Paracetamol and methotrexate model. The study reveals hepatocyte regeneration followed by hepatic restoration in pre-clinical settings. Keywords: Acute liver disease, Sicyos edulis, Silymarin, Methotrexate, Liver enzymes